'Realms so barbarous and cruell': Writing Violence in Early Modern Ireland and England. Issue 336 (July 2014) - Covington, Sarah
Abstract In their tendency to avoid theory and interdisciplinary approaches, anglophone historians have frequently neglected to pay attention to questions of genre, form and narrative in the sources they consult. Such an oversight is unfortunate, for it results in partial readings of those sources, and overlooks the fact that the past itself − even as it is expressed in the most apparently neutral of documents − can never be separable from the telling of it. This essay will begin from the premise of genre to argue that English writings which represented the violence of early modern Ireland and England were significant in revealing the fraught relationship between historical developments and aesthetic representations; if writings on Ireland remained assured and stylistically stable, even when describing the worst of atrocities, the pamphlets, memoirs, or poetry of the English Civil War, decades later, became fragmented as the writing of a more internecine and incomprehensible violence could no longer be contained within traditional formal perimeters. Violence in the 1640s was thus questioned in a way it never had been in Ireland, where the certainty embedded in English writings only conveyed the acceptance of that violence as well. By contrast, language which failed in the face of English Civil War violence was also productive, raising questions that would ultimately influence emerging conceptions of human rights in the face of atrocity.